The Interconnected Arctic - UArctic Congress 2016 - Latola, Kirsi; Savela, Hannele (Springer Polar Sciences, 2017)
climate change; Arctic; vulnerability; environment; marine and terrestrial polar landscapes; indigenous knowledge; tourism